THE UNDERPRICING PHENOMENON IN INITIAL PUBLIC OFFERINGS (IPOS) THROUGH FINANCIAL PERFORMANCE AS A MODERATING VARIABLE IN COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - Steven Steven; Syahbandi Syahbandi; Helma Malini; Giriati Giriati; Karsim Karsim (SEAN Institute, 2023)
This study examines the phenomenon of underpricing in the stock market from 2020 to 2022, focusing on companies conducting initial public offerings (IPOs). When the IPO price is lower than the secondary market price, the stock price rises following the IPO. The study's goal is to investigate the factors that influence IPO underpricing as well as the function of financial performance as a moderator in the relationship between these factors and underpricing. Ownership structure, company size, and financial leverage are the independent variables. The study's findings show that ownership structure and financial leverage have a significant impact on underpricing, although firm size has little effect. Furthermore, while financial performance can mitigate the impact of ownership structure and financial leverage on underpricing, it does not affect the impact of firm size on underpricing. This research provides insights into the factors contributing to underpricing in IPOs and identifies financial performance as a potential solution to mitigate the effects of these factors. This information can be beneficial for companies and investors in making investment decisions in the stock market.